Bioinspired Superwettability Electrospun Micro/Nanofibers and Their Applications. (28th May 2018) - Hou, Lanlan; Wang, Nü; Wu, Jing; Cui, Zhimin; Jiang, Lei; Zhao, Yong
Abstract: Inspired by the self‐cleaning phenomenon in nature biology, superwettable materials systems have been increasingly studied by multidisciplinary scientists in past two decades. Among various fabrication methods, electrospinning technology, with superior capability of comprehensive coordination of surface chemical composition and hierarchical micro/nanostructures, has been proved to be a versatile method to fabricate diverse fibrous materials with superwettability from polymers, ceramics, to composites. This review first introduces the progress of electrospinning technology in generating various hierarchical structured nanofibers. Then, the wetting theory of liquid on fibers and recent approaches toward fabricating bioinspired electrospun micro/nanofibers with superwettability are described. Based on the special wettability to different liquids, the electrospun nanofibrous materials play significant roles in liquid mixtures separations, water collection, unidirectional liquid penetrations, and in environmentally responsive materials. Finally, the challenges and promising prospects on electrospun superwettability nanofibrous materials are highlighted. Abstract : The combination of the electrospinning technique with superwettability surfaces, i.e., superhydrophobic, superhydrophilic, and superoleophobic, has generated a booming development in hierarchical structure fibers and special properties materials. Recent progress on superwetting electrospinning materials and their applications is reviewed, including various oil/water mixtures separation, water collection, liquid unidirectional penetration, and smart response surfaces.